Indigenous Well-Being: An Anishinaabek Youth Leadership Approach - McGregor, Deborah; McGregor, Hillary; Sritharan, Mahisha; King, Lauren; Hall, Nyland (NEIHR National Coordinating Centre, 2024)
Successfully addressing the most challenging issues of our time (climate change, biodiversity loss, and pandemics among them) will require transformative change in all areas of human society. We must embrace new perspectives with respect to our interactions with all life. Indigenous knowledge can aid global society in developing sustainable models for human-nature interaction. Indigenous youth are increasingly expressing solutions that can help put us on a clear path forward. The ongoing paternalistic nature of dominant society nonetheless means that Indigenous youth voice continues to be overlooked in most instances, even in programs that are ostensibly developed for the benefit of Indigenous and other youth. In this article, we place Indigenous youth voice front and centre as we describe an Indigenous youth-designed and led initiative aimed at improving mental health and overall wellbeing of specifically Indigenous youth.